Faith in Philosophy or Philosophy within Faith? - Peperzak, Adriaan T. (Archīum Ateneo, 2024)
The question of the relationship between faith and philosophy opens a new possibility for reading the history of philosophy. Despite modern thought’s emancipation from religious and political authorities, philosophers from Descartes to Kant and Hegel continued to see the connections between their philosophy and the Christian religion as a philosophical question of great importance, although religious practices or theological convictions no longer occupied the center of their search for truth. In asking what kind of philosophy is compatible or incompatible with a philosopher’s attachment to Christian faith, a retrieval of metaphorical and vocative language might open new possibilities for interaction between philosophy and faith.